Kajian Aksiologis Terhadap Nilai-Nilai Etika dalam Bimbingan dan Konseling - Angga Saputra; Rukiyati Rukiyati (Indonesian Journal of Educational Counseling, 2026)
Ethics is an important foundation that guides counselors in their actions and serves as a reference for moral and professional decision-making in the practice of guidance and counseling services. This study aims to analyze ethical values in guidance and counseling. The research method used is a systematic literature review. Data collection techniques were carried out by searching for articles on Google Scholar, Scopus, and Sage using keywords. Data analysis techniques used the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) model, which produced 11 out of 300 research articles selected based on specific inclusion and exclusion criteria that could be analyzed. The results of the analysis show that ethical values such as autonomy, justice, confidentiality, competence, and fidelity are moral foundations that must be realized in guidance and counseling practices in schools. For these values to be effective, counselors need to understand, master, and apply them consistently in their services. The application of ethics enables the creation of a safe, open, fair, and professional service atmosphere, thereby building positive perceptions of guidance and counseling teachers among students.